Image-Based, Fiber Guiding Scaffolds: A Platform for Regenerating Tissue Interfaces - Park, Chan Ho (Mary Ann Liebert, Inc., 2014)
In the oral and craniofacial complex, tooth loss is the most commonly acquired disfiguring injury. Among the most formidable challenges of reconstructing tooth-supporting osseous defects in the oral cavity is the regeneration of functional multi-tissue complexes involving bone, ligament, and tooth cementum. Furthermore, periodontal multi-tissue engineering with spatiotemporal orientation of the periodontal ligament (PDL) remains the most challenging obstacle for restoration of physiological loading and homeostasis. We report on the ability of a hybrid computer-designed scaffold—developed utilizing computed tomography—to predictably facilitate the regeneration and integration of dental supporting tissues. Here, we provide the protocol for rapid prototyping, manufacture, surgical implantation, and evaluation of dual-architecture scaffolds for controlling fiber orientation and facilitating morphogenesis of bone-ligament complexes. In contrast to conventional single-system methods of fibrous tissue formation, our protocol supports rigorous control of multi-compartmental scaffold architecture using computational scaffold design and manufacturing by 3D printing, as well as the evaluation of newly regenerated tissue physiology for clinical implementation.